Oncological aid for colorectal cancer patients in Tomsk area: ways of cancer prevention - L. D. Zhuykova; Yu. I. Tyukalov; A. S. Popova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To estimate level of oncologic aid to patient with colorectal cancer in Tomsk area according to survival parameters.Material and methods. Depersonalized data of the Tomsk area population cancer register on 3173 patients with colorectal cancer diagnosed in 2004–2012 were used. Observed, corrected and relative survival rate were designed by actuarial method.Results. Observed survival rate at colorectal cancer was:1-year — 57,8 and 56,4%, 5-year — 38,1 and 38,2%, 9-year — 36,8 and 37,3% in men and women respectively. Comparison of relative survival rate in Tomsk area and in the USA has demonstrated, that the highest difference in scores was marked for 1-, 2- and 3-years survival rate — by 23,7, 24,4 and 22,3% is higher than in the USA. This difference decease along with time interval increase, making 5,9% at 9-years survival rate.Conclusions. Low rate of colorectal cancer early detection, 1-years survival rate and high scores of disease neglecting testify inefficiency of oncologic aid in Tomsk area at primary diagnostic stage. Actions for its improvement are proposed.